Ileal neuroendocrine tumor with carcinoid syndrome, neoplasia of difficult diagnosis and variable prognosis. - Miranda, Gonzalo (2015)
The neuroendocrine tumor (NET) is of difficult diagnosis due to nonspecific symptoms; management is also a challenge. We present the case of a 78 year-old male who suffered of chronic upper abdominal pain and was admitted to emergency with intestinal obstruction and symptoms of carcinoid syndrome (CS). At surgery an ileal tumor was resected with pathology report of NET positive for chromogranin A and ki 67 proliferative index of 2-3%. The patient continued with CS symptoms and presented high levels of 5-HIAA and liver metastases by MRI. Octreotide was started with good outcome. Experience with this case indicates to be alert at symptoms of functioning NET, due to an increase in its incidence. It is useful to request immunohistochemical markers. Identification of NET with low grade mitosis and proliferation signal good prognosis.